Gender, Islam and the Bugis Diaspora in nineteenth-and twentieth-century Riau - Andaya, Barbara Watson (Universiti Kebangsaan Malaysia, 2003)
The importance of women in maintaining male status is a common theme in academic studies of Bugis society. Presumably, these attitudes would have been embedded in the culture that Bugis migrants brought to the Malay world in the late seventeenth and eighteenth centuries. On the island of Riau, which became the center for Bugis influence in the kingdom of Johor and the larger Malay world, intermarriage between Bugis and Malays meant these gender imperatives were somewhat diluted. Nonetheless, the influence of women of Bugis-Malay descent was still evident in Riau’s ruling circles in the early nineteenth century. During this period, however, new formulations of gender status began to penetrate Islamic society through the reformist and more fundamentalist teachings of the Wahabi. The influence of these teachings, which strengthened existing ambiguity towards the presence of women in public life, are evident in the Tuhfat al-Nafis, the history of the Bugis diaspora written by the great scholar Raja Ali Haji. By the end of the century, the place of well-born women in Riau is less prominent than a hundred years earlier. However, by examining literary and historical sources, this article argues that the environment created on Pulau Penyengat still allowed women a space in which they could write. A synchronic approach to their publications permits us to see how the kinds of questions their works address shifted according to changing times and the new issues raised by Western influence and ideas about ‘modernity’ in the Muslim world